STUDENTS’ SATISFACTION IN USING E-LEARNING DURING THE COVID-19 PANDEMIC - Hermawan, Herry; Nilamsari, Natalina; Achmad, Ardan (Moestopo International Review on Social, Humanities, and Sciences, 2023)
This study considers Transformative Learning Theory of online students. This research aims to evaluate the level of student satisfaction with online learning platforms and learning experiences during the novel coronavirus COVID-19 pandemic. Data were collected through a quantitative study applying online questionnaire carried out in December 2022 – August 2023, using a representative sample (N=104). Findings showed students highly satisfied with the online learning environment and with the school support during COVID-19 pandemic. This study also found that most of the students highly preferred the online learning or the blended learning classroom. The students highly preferred with Zoom as the learning platform and as a course delivery tool. The findings has contributed to the evolving of the Transformative Learning Theory, particularly in online learning in developing contries like Indonesia. This study provides implications to e-education, educators, education institutions, and website system developers of online learning sites dealing with materials and services.